Analisis Semiotika Roland Barthes: Representasi Disonansi Kognitif Tokoh Kiran dalam Film Tuhan, Izinkan Aku Berdosa - Syifaur Rahmah; Reza Abineri; Nasya Puspa Angely; Girinda Fatihu Risqi (MUKASI: Jurnal Ilmu Komunikasi, 2025)
This study aims to analyze the form of cognitive dissonance experienced by the character Kiran and examine the representation of social myths related to women and morality in the film Tuhan, Izinkan Aku Berdosa directed by Hanung Bramantyo. Employing a qualitative approach grounded in critical paradigm, the analysis is conducted through Roland Barthes' semiotics (denotation, connotation, myth) and Leon Festinger's cognitive dissonance framework, focusing on cinematic signs. The findings reveal Kiran's cognitive dissonance to be highly complex, primarily triggered by betrayal and the profound conflict between her deeply held beliefs and harsh reality. She attempts to reduce this dissonance through a radical cognitive shift, transforming her profession into a deliberate tool for revenge against perceived hypocrisy, even extending to a defiance of God. Nevertheless, her inner discomfort remains notably unresolved. Semiologically, the film powerfully debunks prevailing myths that link female morality to outward appearance or environment, alongside myths of religious hypocrisy and female purity that clash starkly with behavior. Moreover, it actively challenges myths of absolute obedience and divine justice. This research enriches the fields of film semiotics and communication psychology, providing profound insights into individual internal conflict and highlighting cinema's potential as a potent medium for social critique, fostering critical reflection on rigid moral standards and societal hypocrisy.